TRANSLATION OF WORDS REPRESENTING THE AUTISTIC CHARACTER IN FLOWERS FOR ALGERNON NOVEL - Trisakti Agriani; MR Nababan; Djatmika Djatmika (Leksema: Jurnal Bahasa dan Sastra, 2018)
This study was aimed at analyzing the Indonesian translation of spelling, punctuation, and grammatical errors made by autistic character in Flower for Algernon novel. It also analyzes Â translation techniques, methods, ideology, qualities of the translation. The method applied was descriptive-qualitative with the data in the form of translated words and phrases indicating spelling, punctuation and grammatical errors made by the autistic character. The primary data sources were Flower for Algernon novel along with its translation version in Indonesian. Meanwhile, the secondary data sources were informants who gave information on the accuracy, acceptability, and readability of translation. The process of collecting data used documentation, questionnaire distribution, and focus group discussion (FGD) technique whereas the sampling technique applied is purposive sampling. The findings of this research show that there are 309 data of words containing spelling, punctuation and grammatical errors. Four translation techniques are used by translator namely graphology normalizations, established equivalent, compensation, and deletion. The translation method used tends to be established equivalent with domestication ideology. The translation of words with errors by graphology normalization techniques produced accurate translations with decreases in acceptability. This is because the translator removes the autism markers from the source language to the target language.